Case Report: Bispecific CD20/CD30-targeted chimeric antigen receptor T-cell therapy for non-Hodgkin’s lymphoma - Yuejiao Huang; Yiming Gong; Xiang Liu; Huaying Ruan; Jinhua Lu; Hosein Kouros-Mehr; Hong Liu; Han Wang (Frontiers in Immunology)
CD19-directed CAR T-cell therapy is a breakthrough immunotherapy for B-cell malignancies. However, CD19 loss-mediated relapsed/refractory disease continues to pose a significant challenge, highlighting the urgent need for CAR T cells targeting alternative antigens. To address this issue, we developed a CD20-directed CAR T incorporated with an additional CD30-directed binder to enhance cytotoxicity toward cancer cells. Here, we report that a patient with bulky transformed follicular lymphoma was successfully treated with CD20/CD30-directed CAR-T cells. The patient received two doses of anti-CD20/CD30-CAR-T therapy administered one month apart. Complete metabolic remission was achieved 1 month after the first infusion without evidence of cytokine release syndrome (CRS) or immune effector cell-associated neurotoxicity syndrome (ICANS). The second dose was given as a consolidation therapy with sustained disease-free survival exceeding 12 months to date. The report underscores the promising therapeutic potential and safety profile of CD20/CD30-directed CAR T-cell therapy.Clinical Trial Registrationhttps://www.clinicaltrials.gov, identifier NCT06756321.